2018
DOI: 10.1007/s00114-018-1564-y
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic evidence for niche partitioning and the influence of anthropogenic disturbance on endemic and introduced rodents in central Madagascar

Abstract: We applied a multi-isotope approach to examine aspects of niche partitioning, competition, and mobility for rodents in the Central Highlands of Madagascar. Specifically, we used carbon (δC), nitrogen (δN), and strontium (Sr/Sr) isotope ratios in bone to investigate diet and mobility for endemic tufted tail rats (Eliurus spp.), and introduced black rats (Rattus rattus) and house mice (Mus musculus) within and outside a fragment of montane humid forest in the Ambohitantely Special Reserve. There was a clear spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…2012; Hartman & Richards 2014; Crowley et al . 2018). Feeding height stratification of this form has been previously proposed as an explanation for the co‐occurrence of megaherbivore taxa in Mesozoic terrestrial systems (Béland & Russell 1978; Mallon et al .…”
Section: Megaherbivore Niche Partitioning In the Oldman Formationmentioning
confidence: 99%
“…2012; Hartman & Richards 2014; Crowley et al . 2018). Feeding height stratification of this form has been previously proposed as an explanation for the co‐occurrence of megaherbivore taxa in Mesozoic terrestrial systems (Béland & Russell 1978; Mallon et al .…”
Section: Megaherbivore Niche Partitioning In the Oldman Formationmentioning
confidence: 99%
“…in which authors found no gender differences in the concentration of various chemical elements in muscle and bone samples [ 80 ]. Likewise, no differences in isotopic values depending on age, sex or breeding condition have been found in several rodent species, including the wood mouse [ 51 , 70 , 74 , 75 , 81 , 82 , 83 , 84 ]. Overall, the non-variation in elemental and isotopic values due to individual traits could be attributed to the observed lack of individual differences in food intake inside traps.…”
Section: Discussionmentioning
confidence: 99%
“…Antler samples were prepared for 87 Sr/ 86 Sr analysis following estalished protocols (Crowley and Wheatley, 2014;Baumann and Crowley, 2015;Crowley et al, 2018). Ca.…”
Section: Strontium Isotope ( 87 Sr/ 86 Sr) Preparation and Analysismentioning
confidence: 99%